Co-constructing learning opportunities in Hong Kong Chinese-as-an-additional-language classroom interactions: a conversation analysis perspective - Tam, Hugo Wing Yu (Nanyang Technological University, 2023)
Recent conversation analytic research has demonstrated how teachers’ and students’ interactional skills for the creation of opportunities for learning have a positive impact on the learning of English in ELT classrooms. However, little empirical research has been conducted into the micro-details of how learning opportunities are co-constructed by teachers and students in Asian language learning classrooms. This thesis focuses on the sequential and embedded organisation of classroom practices in learning Sinitic linguistic knowledge and investigates how language teachers and students jointly create different learning opportunities through talk, material objects, and a range of semiotic and multimodal resources in four secondary schools in multilingual Hong Kong.